A modern analogue of the Pleistocene steppe‐tundra ecosystem in southern Siberia. (31st July 2018) - Chytrý, Milan; Horsák, Michal; Danihelka, Jiří; Ermakov, Nikolai; German, Dmitry A.; Hájek, Michal; Hájková, Petra; Kočí, Martin; Kubešová, Svatava; Lustyk, Pavel; Nekola, Jeffrey C.; Pavelková Řičánková, Věra; et al.
Abstract : Steppe‐tundra is considered to have been a dominant ecosystem across northern Eurasia during the Last Glacial Maximum. As the fossil record is insufficient for understanding the ecology of this vanished ecosystem, modern analogues have been sought, especially in Beringia. However, Beringian ecosystems are probably not the best analogues for more southern variants of the full‐glacial steppe‐tundra because they lack many plant and animal species of temperate steppes found in the full‐glacial fossil record from various areas of Europe and Siberia. We present new data on flora, land snails and mammals and characterize the ecology of a close modern analogue of the full‐glacial steppe‐tundra ecosystem in the southeastern Russian Altai Mountains, southern Siberia. The Altaian steppe‐tundra is a landscape mosaic of different habitat types including steppe, mesic and wet grasslands, shrubby tundra, riparian scrub, and patches of open woodland at moister sites. Habitat distribution, species diversity, primary productivity and nutrient content in plant biomass reflect precipitation patterns across a broader area and the topography‐dependent distribution of soil moisture across smaller landscape sections. Plant and snail species considered as glacial relicts occur in most habitats of the Altaian steppe‐tundra, but snails avoid the driest types of steppe. A diverse community of mammals, including many species typical of the full‐glacial ecosystems, also occurs there. Insights from the Altaian steppe‐tundra suggest that the full‐glacial steppe‐tundra was a heterogeneous mosaic of different habitats depending on landscape‐scale moisture gradients. Primary productivity of this habitat mosaic combined with shallow snow cover that facilitated winter grazing was sufficient to sustain rich communities of large herbivores.